Comment on "How to interpret Onsager cross terms in mixed ionic electronic conductors" by I. Riess, Phys. Chem. Chem. Phys., 2014, 16, 22513. Issue 16 (28th April 2015) - Yoo, Han-Ill; Martin, Manfred; Janek, Juergen
<x xml:space="preserve">Abstract</x> Onsager cross coefficients account for the interaction of ionic and electronic fluxes in mixed conductors.